No easy way out - Lorentz, Dayna (No safety in numbers, 2014)
Teens Marco, Shay, Ryan, and Lexi form new allies in the quarantined mall--as the bodies pile up, the disease mutates, the Senator's authority is questioned, and it becomes clear there's no one to trust.